Penerapan Metode Multi-Arttribute Utilily Theory (MAUT) Dan Rank Order Centroid (ROC) Dalam Pemilihan Bidan Terbaik Puskesmas - Dedi Verianto Laia; Rima Tamara Aldisa (STMIK Budi Darma, 2024)
Midwives are professional health workers who have graduated from midwife education and have been registered in accordance with statutory provisions. In practice, midwives have undergone special training to be able to provide services in the form of midwifery care and in the form of caring for women during pregnancy, childbirth and after they give birth. Apart from that, midwives can also help guide mothers to breastfeed and care for newborns for up to six weeks afterward. So, apart from being able to carry out their own midwifery practice, midwives can also practice in various health facilities, one of which is a hospital. A midwife is a health professional who has an important role in caring for women during pregnancy, childbirth and postpartum. The conclusion is that the determination of the recommendation for selecting the best midwife at the health center using the MAUT method from 7 midwives with 5 criteria and the weight value obtained using the ROC method with the highest result can be alternative A1 with a value of 0.715 and the lowest value is A7 with a value of 0. With the implementation of MAUT and ROC methods in recommending midwives at community health centers using the criteria of skill/expertise, service, responsibility, attitude, age and experience. From the results of calculations using the MAUT method and the criteria weighting values ??using the ROC method, a value of 0.715 was obtained for the main priority order.